Forest Policies and NTFP - Based Livelihoods in India - Need for better Interventions - Pandey, Jyoti (Indian Forester, 2014)
Non-timber forest produce have always been integral part of income and consumption of tribal people. However, their access and usufruct rights to forest resources have been affected by various policies and legislations adopted in pre and post-independence India. As in other parts of the world, there is marked change in forest and NTFP related policies. While earlier, there was a top-down planning for forest management with a clear bias for industrial needs, now there are laudable attempts at devolution of power and conservation of forest wealth while ensuring livelihood concerns of forest dependent communities. After social forestry and JFM, the tenurial rights given to forest dwellers under the FRA 2006 is a step forward in evolution of forest policies in India. The marketing structure for trade in NTFP does not ensure fair returns to the forest dwellers who continue to live in poverty and are unaware of the potential income through value-addition to their produce. There is, thus, a need for a more holistic approach to tap the potential of NTFP's contribution in the tribal/rural economy.